Patterns of Accelerating the Creation of Works of Art: Appropriation of Work Ideas - Sandra, Yofita; Ondira ASa, Ferdian; Pebriyeni, Eliya (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
Art lecturers are challenged to maximize the quality of the work produced by students. Lecturers need a long time to prepare the learning equipment. At the same time, the activities that have to be completed are not only teaching but also researching and implementing community service as well. This article describes how realizing such efforts starts with the lecturers themselves. One of the strategies used to create such a work is to make appropriations. Various sources of reading and events triggered the spirit of the lecturer and spread it to the students. The artistic ideas that can be used to stimulate come from music, literature, and even medicine. The method used in this report is art-based research. It is believed that the process of drawing and building a new structure of the existing work has also succeeded in shortening the time and saving the cost of money. As a result, when a lecturer produces one product, students can develop it into more than two to three varied alternatives. This spirit is an important part of transforming the values of new creativity in art and cultural education. It is highly recommended that lecturers make their work a learning medium before adding other sources and references. To enhance student learning, institutions of higher education must prioritize the development and support of their lecturers. Keywords: acceleration, product, appropriation, artwork, education.